2018
DOI: 10.18632/oncotarget.25509
|View full text |Cite
|
Sign up to set email alerts
|

WNK1 kinase and its partners Akt, SGK1 and NBC-family Na+/HCO3− cotransporters are potential therapeutic targets for glioblastoma stem-like cells linked to Bisacodyl signaling

Abstract: Glioblastoma is a highly heterogeneous brain tumor. The presence of cancer cells with stem-like and tumor initiation/propagation properties contributes to poor prognosis. Glioblastoma cancer stem-like cells (GSC) reside in hypoxic and acidic niches favoring cell quiescence and drug resistance. A high throughput screening recently identified the laxative Bisacodyl as a cytotoxic compound targeting quiescent GSC placed in acidic microenvironments. Bisacodyl activity requires its hydrolysis into DDPM, its pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Further reports have shown that bisacodyl/ DDPM triggers necrosis in quiescent GSCs by inhibiting InsP3-induced Ca 2þ release [66]. Moreover, DDPM endows cytotoxic effects by suppressing the activity of a kinase cascade composed of WNK1 and its upstream regulators, AKT and SGK1, triggering a subsequent increase in NBC family Na þ /HCO3cotransporter activity [67]. These findings support the utility of DDPM as a potential therapeutic agent for specifically targeting resistant quiescent cancer stem-like cells.…”
Section: Bisacodylmentioning
confidence: 52%
See 1 more Smart Citation
“…Further reports have shown that bisacodyl/ DDPM triggers necrosis in quiescent GSCs by inhibiting InsP3-induced Ca 2þ release [66]. Moreover, DDPM endows cytotoxic effects by suppressing the activity of a kinase cascade composed of WNK1 and its upstream regulators, AKT and SGK1, triggering a subsequent increase in NBC family Na þ /HCO3cotransporter activity [67]. These findings support the utility of DDPM as a potential therapeutic agent for specifically targeting resistant quiescent cancer stem-like cells.…”
Section: Bisacodylmentioning
confidence: 52%
“…Accumulating evidence indicates that DDPM, the active metabolite of bisacodyl, induces necrosis of quiescent human glioblastoma stem-like cells (GSCs) in vivo and in vitro without exerting deleterious effects on non-cancer neural cells [5,66]. In particular, microenvironment acidification of cultured GSCs induces cell cycle arrest and sensitization to DDPM [66,67]. Further reports have shown that bisacodyl/ DDPM triggers necrosis in quiescent GSCs by inhibiting InsP3-induced Ca 2þ release [66].…”
Section: Bisacodylmentioning
confidence: 99%
“…The best compounds exhibited anti-inflammatory activities at 10 µM using zebrafish model. Recently, Zeniou and co-workers described the potentialities of bisacodyl and its desacetylated metabolite DDPM to target glioblastoma cancer stem-like cells in their quiescent, more resistant state [8][9]. Taking into account the literature data concerning the new therapeutic applications of bisacodyl, we report herein the antibacterial activity of bisacodyl and its deacetylated metabolite DDPM using new pathogens strains.…”
Section: Introductionmentioning
confidence: 97%
“…intestinal to the vascular side leading to the development of diarrhea [5]. Bisacodyl has been also described for its antibacterial, [6] anti-inflammatory [7] and anticancer activities [8][9] In 2015 Sylla and coworkers described for the first time the antibacterial activity of bisacodyl against Grampositive and Gram-negative pathogenic strains [6]. Bisacodyl showed an excellent antimicrobial activity (MIC values of 6.25-12.5 µg/mL; 3.125-12.5 µg/mL and 6.25-12.5 µg/mL against Grampositive strains Micrococcus, Staphylococcus and Listeria respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Slc4a4, the gene that encodes NBCe1, is regulated by hypoxia in several epithelial cancer cell lines, but not in glioblastoma cell lines [ 12 ]. In quiescent glioblastoma cancer stem-like cells maintained in an acidic environment, WNK1-dependent NBC phosphorylation has been proposed to be linked to their response to treatment approaches [ 13 ]. However, the adaptation of pH regulatory proteins (specifically NBCs) in well-characterised tumour cell subpopulations, to changes in the tumour microenvironment has not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%